Discovery of New Non‐Steroidal Farnesoid X Receptor Modulators Through 3D Shape Similarity Search and Structure‐Based Virtual Screening. (10th October 2014) - Wang, Lei; Si, Pei; Sheng, Yayun; Chen, Yingjie; Wan, Ping; Shen, Xu; Tang, Yun; Chen, Lili; Li, Weihua
<x xml:space="preserve">Abstract</x> As a ligand‐activated transcriptional factor, farnesoid X receptor (FXR) has a variety of biological functions, such as biosynthesis of bile acids, metabolism of lipid, and glucose homeostasis, and thus is related to multiple diseases, especially metabolic syndrome. In this study, to discover new FXR modulators, we have designed a strategy by combining 3D shape similarity search and structure‐based docking methods. Taking two FXR ligands that we previously reported as the reference molecules, virtual screening was performed against the Enamine database, and finally 59 compounds were selected for bioassay. Among them, four compounds exhibited agonistic or antagonistic activities against FXR in homogeneous time resolved fluorescence assay. Two of them were found to be new, potent FXR antagonists in cell‐based assay with IC50 values of 8.39 and 6.53 μm, respectively.